Avaliação da estabilidade oxidativa de biodiesel e diesel comercial com adição de biodiesel - Kalat, Fabio (2017)
Fossil fuel energy sources are slowly being replaced by renewable fuels - including biodiesel, which has gained spotlight when it is incorporated with regular diesel oil. Biodiesel causes less damage to the environment, due to its biodegradation effect, sometimes producing undesirable effects. Oxidation stability is the resistance a sample has to oxidize, and allows an analysis of its chemical structure and feedstock quality. The lack of data in this matter created a need for specific equipment, but they are costly. Because of that, studies of alternative ways to acquire preliminary oxidative data are needed. This paper has the intention to monitor the induction period (time required for an oil to start degradation by oxidation - IP) using Rancimat equipment. It was possible to obtain the IP of diesel (8 h and 42 min) which is more stable than biodiesel (8 h and 3 min). Mixtures of diesel/biodiesel were diluted in two solvents: n-hexane and isooctane. They were analyzed using a uv-vis spectrometer, and the results showed an increase of absorbance of 69% for commercial diesel (0.190 to 0.310 abs) and 77% for commercial biodiesel (1.695 to 3 abs). Readily available equipment, like a spectrophotometer to make a primary analysis is shown to be possible, in order to analyze the accelerated oxidation tests (caused by heat treatment).